Analisis Yuridis Ketiadaan Pemberian Restitusi bagi Korban Kekerasan dalam Rumah Tangga (KDRT) dalam Putusan Nomor 146/Pid.Sus/2022/PN Cbn Berdasarkan Peraturan Mahkamah Agung Nomor 1 Tahun 2022 - Rayhan Prakasa Putra; Agus Dimyati (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the judge's considerations in Decision Number 146/Pid.Sus/2022/PN Cbn and the appropriateness of the lack of restitution for victims of domestic violence based on Supreme Court Regulation Number 1 of 2022. The research method used is normative juridical with a statutory approach and a case approach. The results show that the judge was correct in proving the defendant's guilt and imposing a sentence, but did not consider the victim's recovery aspect. The absence of restitution is procedurally not contrary to PERMA Number 1 of 2022 because there was no request for restitution, but indicates that the fulfillment of the victim's right to obtain restitution is not optimal.